2006
DOI: 10.1038/sj.bjc.6603298
|View full text |Cite
|
Sign up to set email alerts
|

Mapping loss of heterozygosity in normal human breast cells from BRCA1/2 carriers

Abstract: We have studied loss of heterozygosity at the BRCA1 and BRCA2 loci in 992 normal cell clones derived from topographically defined areas of normal tissue in four samples from BRCA1/BRCA2 mutation carriers. The frequency of loss of heterozygosity in the clones was low (1.01%), but it was found in all four samples, whether or not a tumour was present. Topographical mapping revealed that the genetic changes were clustered in some breast samples. Our study confirms the previous finding that a field of genetic insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…2). Previous studies using low-resolution genetic analysis reported that allelic imbalance is increased threefold in normal breast epithelium from BRCA1 mutation carriers, compared to controls (Larson et al, 2005;Clarke et al, 2006). Recently, Rennstam et al (2010) used high-resolution arraybased comparative genomic hybridization to show that genomic alterations in histopathologically normal breast tissue from BRCA1 mutation carriers are more frequent than in the normal breast tissue of age-matched controls.…”
Section: Discussionmentioning
confidence: 95%
“…2). Previous studies using low-resolution genetic analysis reported that allelic imbalance is increased threefold in normal breast epithelium from BRCA1 mutation carriers, compared to controls (Larson et al, 2005;Clarke et al, 2006). Recently, Rennstam et al (2010) used high-resolution arraybased comparative genomic hybridization to show that genomic alterations in histopathologically normal breast tissue from BRCA1 mutation carriers are more frequent than in the normal breast tissue of age-matched controls.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, LOH is a stochastic event in BRCA1 mut/+ patients, affecting the mutant or wild-type alleles at similar frequencies (Clarke et al, 2006). Since the analysis of prophylactic mastectomy tissues showed differentiation defects in significant proportions of the breast tissue, this suggests that LOH was not likely responsible for the perturbations in breast epithelial differentiation or basal tumor phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is the first report on the loss of the Mutp53 allele through LOH in an apparent healthy tissue, Mut-LOH was noticed for other TSGs with a role in DNA repair. [41][42][43][44][45] It is tempting to speculate that LOH can be seen as a physiological genetic repair mechanism. Gene expression, copy number and sequencing analyses (Figures 6f, 2e, f and h) point to the induction of HRDRP events as the mechanism underlie most cases of LOH.…”
Section: Discussionmentioning
confidence: 99%